KECERDASAN EMOSI, INTELIGENSI, DAN PRESTASI BELAJAR SISWA SEKOLAH MENENGAH ATAS - Muslimah Zahro Romas (Jurnal Psikologi, 2007)
Ninety nine students grade 11 participated on this study in order to understand the relationship between emotional intelligence, cognitive intelligence, and student’s school performance. The former two variables were the independent variable whilst die third was the dependent variable. This study revealed that there was no relationship emotional intelligence and school performance although student's cognitive intelligence was controlled. It was found that there was no relationship between student's cognitive intelligence and school performance although the emotional intelligence was controlled. The last result showed that there was no relationship among those three variables. According Bloom, school performance was more likely influenced by the question type of the school exam rather than the emotional and cognitive intelligences.